Implementasi Metode Exponensial Smooting dalam Memprediksi Harga Logam Mulia Emas Optimasi Abadi (Eoa Gold) - Gusmanley; Corry Sormin (JURNAL RISET AKUNTANSI JAMBI, 2023)
Precious metals are one of the best investment choices and are currently still the prima donna in people's lives. The development of the times has caused precious metals, especially bars, to appear with various brands, one of which is Eoa Gold, which has advantages over other LMs. The price of precious metals always changes from time to time and the demand for it in Indonesia is increasing, so one solution is needed, namely forecasting Gold prices in Indonesia. This aims to find out the price of precious metals that will come. The forecasting method in this study uses the Single Exponential Smoothing method which can perfect a forecasting result by smoothing past values which function to produce forecasting values. The data used is time series data from January 1 2022 to December 31 2022 for 12 months. Then, in this study, the SES analysis uses the parameters dan ,, then evaluates the error value of the forecasting results with the Mean Absolute Percentage Error (MAPE). The lowest MAPE results obtained were when the parameter for all Eoa Gold sizes with values of 0,44%, 0,43%, 3,74% and 0,51%. Based on the MAPE value criteria, it is concluded that the Single exponential smoothing method is very accurate in forecasting the price of Eoa Gold.